CAFF CBMP Report No. 9: Community-based Monitoring – a discussion paper - Torikka-Gelencsér, R.; Fleener, C.; Gofman, V.; Peskov, V.; Retter, G.-B. (CAFF International Secretariat, 2004)
Community-based Monitoring – a discussion paper. Supporting publication to the CAFF Circumpolar Biodiversity Monitoring Program – Framework Document. CAFF CBMP Report No. 9